Proliferation and TH1/TH2 Cytokine Production in Human Peripheral Blood Mononuclear Cells after Treatment with Cypermethrin and Mancozeb In Vitro - Rajesh Mandarapu; Rajanna Ajumeera; Vijayalakshmi Venkatesan; Balakrishna Murthy Prakhya (Journal of Toxicology)
In recent times, human cell-based assays are gaining attention in assessments of immunomodulatory effects of chemicals. In the study here, the possible effects of cypermethrin and mancozeb on lymphocyte proliferation and proinflammatory (tumor necrosis factor (TNF-) α) and immunoregulatory cytokine (interferon- (IFN-) γ, interleukins (IL) 2, 4, 6, and 10) formation in vitro were investigated. Human peripheral blood mononuclear cells (PBMC) were isolated and exposed for 6 hr to noncytotoxic doses (0.45–30 µM) of cypermethrin or mancozeb in the presence of activating rat S9 fraction. Cultures were then further incubated for 48 or 72 hr in fresh medium containing phytohemagglutinin (10 µg/mL) to assess, respectively, effects on cell proliferation (BrdU-ELISA method) and cytokine formation (flow cytometric bead immunoassays). Mancozeb induced dose-dependent increases in lymphocyte proliferation, inhibition of production of TNFα and the TH2 cytokines IL-6 and IL-10, and an increase in IFNγ (TH1 cytokine) production (at least 2-fold compared to control); mancozeb also induced inhibition of IL-4 (TH2) and stimulated IL-2 (TH1) production, albeit only in dose-related manners for each. In contrast, cypermethrin exposure did not cause significant effects on proliferation or cytokine profiles. Further studies are needed to better understand the functional significance of our in vitro findings.